Biochemically validated structural model of the 15‐subunit intraflagellar transport complex IFT‐B. (10th November 2022) - Petriman, Narcis A; Loureiro‐López, Marta; Taschner, Michael; Zacharia, Nevin K; Georgieva, Magdalena M; Boegholm, Niels; Wang, Jiaolong; Mourão, André; Russell, Robert B; Andersen, Jens S; Lorentzen, Esben
Abstract: Cilia are ubiquitous eukaryotic organelles impotant for cellular motility, signaling, and sensory reception. Cilium formation requires intraflagellar transport of structural and signaling components and involves 22 different proteins organized into intraflagellar transport (IFT) complexes IFT‐A and IFT‐B that are transported by molecular motors. The IFT‐B complex constitutes the backbone of polymeric IFT trains carrying cargo between the cilium and the cell body. Currently, high‐resolution structures are only available for smaller IFT‐B subcomplexes leaving > 50% structurally uncharacterized. Here, we used Alphafold to structurally model the 15‐subunit IFT‐B complex. The model was validated using cross‐linking/mass‐spectrometry data on reconstituted IFT‐B complexes, X‐ray scattering in solution, diffraction from crystals as well as site‐directed mutagenesis and protein‐binding assays. The IFT‐B structure reveals an elongated and highly flexible complex consistent with cryo‐electron tomographic reconstructions of IFT trains. The IFT‐B complex organizes into IFT‐B1 and IFT‐B2 parts with binding sites for ciliary cargo and the inactive IFT dynein motor, respectively. Interestingly, our results are consistent with two different binding sites for IFT81/74 on IFT88/70/52/46 suggesting the possibility of different structural architectures for the IFT‐B1 complex. Our data present a structural framework to understand IFT‐B complex assembly, function, and ciliopathy variants. Synopsis: Construction and maintenance of cilia is mediated by the the bidirectional trafficking of 22 different proteins organized into IFT‐A and IFT‐B complexes, with only structures of smaller IFT‐B assemblies solved. Here, a combination of Alphafold structural modeling and biochemical analysis offers a structural model of the 15‐subunit IFT‐B complex. Validated structural model for 15‐subunit IFT‐B reveals an elongated and highly flexible complex consistent with cryo‐electron tomographic reconstructions of IFT trains. The IFT‐B complex divides into IFT‐B1 and IFT‐B2 parts with binding sites for ciliary cargo and the inactive IFT dynein motor, respectively. Structural modeling and biochemical data are consistent with two different binding sites for IFT81/74 on IFT88/70/52/46 suggesting the possibility of two different conformations of the IFT‐B1 complex. Abstract : A combination of alphafold structural modeling and biochemical experiments reveals the structure of the large IFT‐B intraflagellar transport complex and offers insight into IFT‐B complex assembly and cilia formation.